Parallel Weibull regression model. - Arasan, Jayanthi (Universiti Putra Malaysia Press, 2008)
This paper focuses on the lifetime analysis of parallel systems consisting of Weibull components with independent failures and covariates. The performance of the parameter estimates of two and three-component parallel systems at different values of the shape parameter, σ, are compared and some confidence interval procedures are analyzed via a coverage probability study for m = 2, using simulated data.